2014
DOI: 10.1093/cid/ciu521
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Gentamicin Plus Azithromycin and Gemifloxacin Plus Azithromycin as Treatment of Uncomplicated Gonorrhea

Abstract: Gentamicin/azithromycin and gemifloxacin/azithromycin were highly effective for treatment of urogenital gonorrhea. Gastrointestinal adverse events may limit routine use. These non-cephalosporin-based regimens may be useful alternative options for patients who cannot be treated with cephalosporin antimicrobials. Additional treatment options for gonorrhea are needed. Clinical Trials Registration. NCT00926796.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
118
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(125 citation statements)
references
References 26 publications
6
118
0
1
Order By: Relevance
“…Preliminary findings from a recent American study examining the effectiveness of the combination of gentamicin with azithromycin suggested high efficacy of this regimen (11). However, this study did not determine the efficacy of the individual antibiotics or of gentamicin for extragenital infections.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Preliminary findings from a recent American study examining the effectiveness of the combination of gentamicin with azithromycin suggested high efficacy of this regimen (11). However, this study did not determine the efficacy of the individual antibiotics or of gentamicin for extragenital infections.…”
mentioning
confidence: 91%
“…Gentamicin has been used for the past 2 decades in the management of gonorrhea in Malawi (8,9). Gentamicin has been considered an option for the treatment of infections due to the MDR and XDR strains and for future treatment of gonorrhea particularly in dual therapy in other geographic regions (10)(11)(12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were no antagonistic outcomes with either of the antibiotics when used to assess the in vitro growth of N. gonorrhoeae, and this may be an important observation for using fluoroquinolones other than ciprofloxacin in combination with azithromycin. A recently completed clinical trial demonstrated 100% and 99.5% successes in patients with uncomplicated gonorrhea infections receiving azithromycin combined with gentamicin or gemifloxacin, respectively (8). In vitro assessments with antibiotic combinations were not performed in that study, but our data support the observed clinical utility of these antibiotic combinations.…”
mentioning
confidence: 57%
“…Injectable ceftriaxone, in combination with oral azithromycin, is now the last antibiotic remaining as recommended firstline treatment [7]. Although other antibiotics are being tested for their safety and efficacy for N. gonorrhoeae treatment [8], no new classes of antibiotics are currently available [4] and management of antibiotics is urgently needed to preserve their efficacy. The current management strategy tries to counteract resistance spread by expanded screening and treatment of hosts [9,10], but the outcome of this strategy is uncertain.…”
Section: Introductionmentioning
confidence: 99%